TRANSLATION ISSUES OF GERMAN AND UZBEK FOOD NAMES (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article is devoted to the analysis of cultural features encountered in the translation process of food names existing in the Uzbek and German languages, as well as to the identification of the problems arising in this process. The article presents examples of translating food names through several types of translation and examines, in a comparative aspect, the semantic features of national food names, their degree of equivalence, and the methods used in translation. Special attention is also paid to the issues of rendering food names through transliteration, descriptive translation, and alternative equivalents. Through the comparative analysis of food-related terms in the Uzbek and German languages, their conceptual differences and common features are revealed. In particular, the article analyzes how intercultural differences may cause semantic inaccuracies in the translation process. The results of the study serve as an important scientific source for the fields of literary translation, linguoculturology, and comparative linguistics.